Outcomes in AB0 Incompatible Living Donor Kidney Transplantation: A Case – Control Study - Cozzi, Martina; Donato, Paola; Ugolini, Gabriele; Nguefouet Momo, Rostand Emmanuel; Nacchia, Francesco; Ballarini, Zeno; Piccoli, Pierluigi; Cantini, Maurizio; Caletti, Chiara; Andreola, Stefano; Gandini, Giorgio; Gambaro, Giovanni; et al. (Frontiers in Medicine, 2022)
Background: Patients waiting for a kidney transplant by far exceed available organs. AB0 incompatible living donor kidney transplantation (AB0i LDKT) represents ad additional effective option, but with higher risk of complications. We aimed at evaluating outcomes of AB0i LDKTs compared to compatible (AB0c) controls at our Institution. Methods: Retrospective matched case – control study (1:2) comparing AB0i vs AB0c LDKTs from March 2012 to September 2021. Considered outcomes: graft function, acute rejections, sepsis, CMV infection, BK virus reactivation, death-censored graft survival, patient survival. Results: 17 AB0i LDKTs matched to 34 AB0c controls. We found excellent graft function, comparable in the two groups, with an eGFR (ml/min/1.73m2) of 67 vs 66 at 1 year (p=0.41), 63 vs 64 at 3 years (p=0.53). AB0i recipients had a statistically significant higher incidence of acute rejection, antibody-mediated rejection and sepsis within 30 days, 1 and 3 years after surgery. There was no difference in CMV infection, BK virus reactivation, death-censored graft survival between the two groups. Patient survival was inferior in AB0i group at 1 and 3 years (88,2% vs 100%) (log-rank p=0.03) due to early death for opportunistic infections. AB0i LDKTs spent longer time on dialysis (p=0.04) and 82,3% vs 38,3% controls had blood group 0 (p=0.003). Conclusions: AB0i LDKT is an effective therapeutic strategy with graft function and survival comparable to AB0c LDKTs, despite higher rates of acute rejection and sepsis. It is an additional opportunity for patients with less chances of being transplanted, as blood group 0 individuals.